Description of Sarcocystis scandentiborneensis sp. nov. from treeshrews (Tupaia minor, T. tana) in northern Borneo with annotations on the utility of COI and 18S rDNA sequences for species delineation - Ortega Pérez, Paula (Int J Parasitol Parasites Wildl, 2020)
Sarcocystis scandentiborneensis sp. nov. was discovered in histological sections of striated musculature of treeshrews (Tupaia minor, T. tana) from Northern Borneo. Sarcocysts were cigar-shaped, 102 μm–545 μm long, and on average 53 μm in diameter. The striated cyst wall varied in thickness (2–10 μm), depending on whether the finger-like, villous protrusions (VP) were bent. Ultrastructurally, sarcocysts were similar to wall type 12 but basal microtubules extended into VPs that tapered off with a unique U-shaped, electron-dense apical structure. In phylogenetic trees of the nuclear 18S rRNA gene, S. scandentiborneensis formed a distinct branch within a monophyletic subclade of Sarcocystis spp. with (colubrid) snake-rodent life cycle. We mapped all intraspecific (two haplotypes) and interspecific nucleotide substitutions to the secondary structure of the 18S rRNA gene: in both cases, the highest variability occurred within helices V2 and V4 but intraspecific variability mostly related to transitions, while transition/transversion ratios between S. scandentiborneensis, S. zuoi, and S. clethrionomyelaphis were skewed towards transversions. Lack of relevant sequences restricted phylogenetic analysis of the mitochondrial Cytochrome C oxidase subunit I (COI) gene to include only one species of Sarcocystis recovered from a snake host (S. pantherophisi) with which the new species formed a sister relationship. We confirm the presence of the functionally important elements of the COI barcode amino acid sequence of S. scandentiborneensis, whereby the frequency of functionally important amino acids (Alanine, Serine) was markedly different to other taxa of the Sarcocystidae. We regard S. scandentiborneensis a new species, highlighting that structurally or functionally important aspects of the 18S rRNA and COI could expand their utility for delineation of species. We also address the question why treeshrews, believed to be close to primates, carry a parasite that is genetically close to a Sarcocystis lineage preferably developing in the Rodentia as intermediate hosts.